Rats with congenital learned helplessness respond less to sucrose but show no deficits in activity or learning - Vollmayr, Barbara; Bachteler, Daniel; Vengeliene, Valentina; Gass, Peter; Spanagel, Rainer; Henn, Fritz A. (Behavioural brain research, 2004)
Inbred rat strains for congenital learned helplessness (cLH) and for congenital resistance to learned helplessness (cNLH) were investigated as a model to study genetic predisposition to major depression. Congenitally helpless rats respond less to sucrose under a progressive ratio schedule. This is not confounded by locomotor hypoactivity: in contrast, cLH rats show a slight hyperactivity during the first 5min of an open field test. cLH rats acquire operant responding to sucrose as readily as cNLH rats and exhibit normal memory acquisition and retrieval in the Morris water maze, thus ruling out general learning deficits as the cause of the decreased response to sucrose. Reduced total responses and reduced breaking points for sucrose in the cLH strain argue for anhedonia, which is an analogue to loss of pleasure essential for the diagnosis of major depressive episodes, and thus confirm the validity of congenitally learned helpless rats as a model of major depression.
Online 22 September 2003
Gesehen am 03.11.2020